FAKTOR PENDORONG DAN PENGHAMBAT MEWUJUDKAN MODEL SINERGIS PENGEMBANGAN WILAYAH TAPAL KUDA MENJADI KESATUAN DAERAH PERENCANAAN DI ERA OTONOMI DAERAH - Djoko Soejono; Agus Supriono; Julian Adam Ridjal (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2011)
Central issue leading this research is on optimistic way of thinking that there is possibility of policy model formulation alternative that can synergy any interests in order to actualize Horse Shoe area in East Java province into regional planning unit under the importance of regional autonomy policy implementation. The problem being researched are: (a) what critical factors that can be as trigger and inhibitor factors are, and (b) how the formulation of alternative model of policy can be viewed as effective and efficient. The approach of analysis being used is descriptive and qualitative. Based on the research, this can be identified into 6 critical factors of political aspect, 8 economic aspects, 3 social aspects and 7 institutional aspects that can be viewed as the potential for trigger factors. Thus with that there are 4 critical factors of political aspect, 3 economic aspect, 2 social aspect, and 3 institutional aspect that can be viewed as the potential for inhibitor aspects. Alternative of policy model that can be considered to be effective is model of integrated economic development of reliable zone on specific of locality base.Key Words: integrated economic, East Java province